Structural Transformations in Agriculture as Necessary Condition for Sustainable Rural Development in Ukraine - STROCHENKO, Natalia; KOBLIANSKA, Inna; MARKOVA, Olena (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The article highlights the contradiction between the current state of agriculture in Ukraine and ecological and socio-economic objectives of sustainable rural development. It is justified the necessity of transition from the industrial model of agriculture to the model of local end-use products markets. It is proved the necessity to improve the mechanisms of state support for agriculture to stimulate the production of consumer basket products as well as the application of marketing approach in the development of local markets of such products. There are formulated the measures to improve the safety and food quality regulatory system to identify the agri-food products as object of marketing.